Peran Regulasi Emosi dalam Memprediksi Efikasi Diri pada Warga Binaan Pemasyarakatan Perempuan - Aniela, Clarisa; Soetikno, Naomi (Jurnal Ilmiah Psikologi (JIPSI), 2024)
Female inmates face the challenge of emotion regulation in their daily lives in correctional institutions. Emotion regulation includes awareness, understanding, acceptance of emotions, impulse control, ability to act according to goals, and flexible use of emotions. Emotion regulation is known to have a role in predicting self-efficacy. This study aims to understand the role of emotion regulation in predicting self-efficacy in female inmates. This research is a predictive correlational quantitative research using convenience sampling and simple regression techniques. The measuring instruments used are Difficulties in Emotion Regulation Scale Short Forms (DERS-SF) and General Self-Efficacy Scale (GSES), which have been adapted to the Indonesian language and modified to suit the context of this study. Results showed that emotion regulation has a role in predicting self-efficacy by 16.4%. These findings are expected to be useful in planning guidance, especially through training to develop emotion regulation and self-efficacy for inmates.